(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
A discussion is presented of the methodological approach to assessment of stability of geologic environment in regions where nuclear cycle objects are located. A basis of assessment is the registration of dynamics of variation of the various factors and exterior energy in a hierarchical block of geologic environment.